High performance of Mg3Bi1.5Sb0.5 based materials for power generation: Revealing the counter-intuitive effect of tuning Bi content on the thermoelectric properties - Nuo Qu; Yuke Zhu; Jianbo Zhu; Kuai Yu; Fengkai Guo; Zihang Liu; Qian Zhang; Wei Cai; Jiehe Sui (Journal of Magnesium and Alloys)
Recently, Mg3Sb2-xBix alloys have attracted intensive attention, with the aim of maximizing the electrical transport performance via donor element doping, increasing the grain size, as well as electronic band structure engineering. However, less attention has been paid to other significant factors, like how these intrinsic point defects and accompanied secondary phases influence thermoelectric properties. In this study, the microstructure and thermoelectric transport properties of Mg3.2Sb0.5Bi1.495-xTe0.005 (x = 0 ∼ 0.2) compounds were systematically investigated, where tuning the Bi content shows the counter-intuitive impact on the thermoelectric properties. It was found that the Bi-poor environment associated with Bi impurities facilitated the increment of cation vacancy formation energy and then increased the carrier concentration, leading to the enhancement of power factor. Simultaneously, the reduction of Bi-rich second phase content weakened the carrier scattering by grain boundaries whereas high carrier mobility was maintained. Moreover, the bipolar thermal conductivity decreased obviously due to the increased majority carrier concentration to suppress the intrinsic excitation. The synergistic optimization pushes the average ZT value (300–573 K) up to 0.95 in the Mg3.2Sb0.5Bi1.295Te0.005 sample. Moreover, the calculated single-leg conversion efficiency is increased up to 9.7% with the hot-side temperature of 573 K, as the record-high value in this system.